Public Information Dispute Resolution (Perspective of the State Administrative Court Act and the Public Information Disclosure Act) - Baruna Poking Bagus Saputro (Unnes Law Journal, 2021)
The specification in the study uses a qualitative analytical descriptive approach and uses a type of doctrinal legal research with normative legal research methods on synchronization and fair legal efforts in resolving public information disputes. The results of research and discussion in the thesis are: First, contains synchronization of public information dispute settlement based on the Law of the Republic of Indonesia Number 5 of 1986regardingState Administrative Courts as amended by Law of the Republic of Indonesia Number 9 of 2004 and most recently by Law Republic of Indonesia Number 51 of 2009 with Law of the Republic of Indonesia Number 14 of 2008 regardingPublic Information Openness. Second, it contains legal remedies that are fair in resolving public information disputes. Conclusions based on the results of research and discussion include: First, synchronizing the settlement of public information disputes based on the Law of the Republic of Indonesia Number 5 of 1986 regarding State Administrative Courts as amended by the Law of the Republic of Indonesia Number 9 of 2004 and most recently by the Republic of Indonesia Law Indonesia Number 51 of 2009 with the Law of the Republic of Indonesia Number 14 of 2008 regardingPublic Information Openness can be done with a juridical analysis of the competence and position of the State Administrative Court and Information Commission, as well as legal synchronization of the relevant Law. Second, fair legal efforts in resolving public information disputes are carried out by juridical analysis based on the theory of justice. Finally, the author gives advice in the form of legislative review efforts to amend the relevant Law, based on apolitical configuration in democratic orders to be able to produce responsive legal products for the realization of legal certainty and justice.